Coordination of the Space and Time of Local Elections with the Space and Time of Makassar City Government in Shaping the Political Practices of Makassar City Government Bureaucracy - Johansyah, Olan Nur Rakhmat; Yakub, Andi; Kambo, Gustiana Anwar (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2024)
The political practice of the Makassar City Government Bureaucracy in Pilkada is an important aspect of the separation of politics and bureaucracy. Anthony Giddens' structuration theory is used as a perspective in this research. "How is the political practice of the Makassar City government bureaucracy in the Makassar City Pilkada?" is the question in this research. Qualitative-descriptive is the method used in this research, using field research and literature to obtain data related to the theme of this research. The results showed that the political practices of the Makassar city government bureaucracy occurred due to the duality of structures that occurred between bureaucrats as agents and rules as structures. The Regional Head as the Personnel Supervisory Officer (PPK) in the Region automatically has dominance over bureaucrats, so that political practice by the bureaucracy is a dialectic of control in seeing the structure of domination.